Spiritually Oriented Couple, Marriage and Family Therapies - Şeyda Çetintaş; Halil Ekşi (Spiritual Psychology and Counseling)
In this review, it is aimed to focus on the integration of spirituality into family-oriented psychological help processes. To conceptualize the reflection of spirituality on the family system more clearly and to make sense of the spirituality-family relationship, the issue of spirituality was examined in specific processes such as in the relationship between parents and children, between spouses and in the transition process from adolescence to late age. The paradoxical nature of spirituality in family relationships was emphasized. For this purpose, spirituality was discussed both as a source of problems and as a source for solutions in family relations. Spiritually oriented psychological clinical help is an emerging field in Turkey. Seeing that spirituality is such an important issue in family relations and marriage, it is aimed to bring a family-focused approach to the spiritually oriented psychological help process. So, by addressing ethical issues, this review aims to offer a new perspective to field practitioners working with couples and families in clinical practice.